Approximation algorithm for dynamic facility location problem - Zhang, Li; Li, Qiaoliang (Journal of combinatorial optimization, 2025)
In this paper, we consider dynamic facility location problem with unit demand (DFLPUD). We propose a 1.52-approximation algorithm that skillfully integrates dual-fitting and greedy augmentation schemes. Our algorithmic framework begins by formulating DFLPUD as a set covering linear integer programming problem. Then we scale the opening cost of all facilities and use the solution of dual-fitting algorithm to seed a local search to yield an improved performance guarantee 1.52. To the best of our knowledge, this is the best known approximation ratio for DFLPUD.